2012
DOI: 10.1002/rcm.6451
|View full text |Cite
|
Sign up to set email alerts
|

Using dissociation energies to predict observability of b‐ and y‐peaks in mass spectra of short peptides. II. Results for hexapeptides with non‐polar side chains

Abstract: RATIONALE The hypothesis that dissociation energies can serve as a predictor of observability of b- and y-peaks is tested for seven hexapeptides. If the hypothesis holds true for large classes of peptides, one would be able to improve the scoring accuracy of peptide identification tools by excluding theoretical peaks that cannot be observed in practical product ion spectra due to various physical, chemical or thermodynamic considerations. METHODS Product ion m/z spectra of hexapeptides AAAAAA, AAAFAA, AAAVAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The sensitivity and specificity of mass spectrometry-based peptide, protein, and microorganism identification can potentially be aided by employing reliable data for peptide fragmentation profiles. These profiles can be made available not only through physical modeling of peptide fragmentation process or through building of extensive spectral libraries, but also by employing deep learning algorithms to predict fragmentation profiles for each precursor on-the-fly. This can be especially useful for data-independent acquisition (DIA) proteomics.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity and specificity of mass spectrometry-based peptide, protein, and microorganism identification can potentially be aided by employing reliable data for peptide fragmentation profiles. These profiles can be made available not only through physical modeling of peptide fragmentation process or through building of extensive spectral libraries, but also by employing deep learning algorithms to predict fragmentation profiles for each precursor on-the-fly. This can be especially useful for data-independent acquisition (DIA) proteomics.…”
Section: Introductionmentioning
confidence: 99%
“…Computational chemistry using density function theory (DFT) to rationalize and predict peptide fragmentation was pioneered by several groups; much of this early work concerned small singly protonated systems. Later analyses of larger and more highly charged systems followed. , Combined guided ion beam MS experimental studies together with theory , have supplemented these data for singly protonated aliphatic di- and tripeptide systems. Single-system, doubly protonated peptide calculations provided evidence that amide bond cleavage barriers vary with position with a balance of charge–solvation and charge–charge repulsion being set. ,, Paizs and coauthors provided evidence from calculations, infrared multiple photon dissociation (IRMPD) spectroscopy, and hydrogen/deuterium exchange experiments which indicated that the b 2 fragments generated from a series of class I tryptic doubly protonated peptides of varying composition generated oxazolone b 2 ion structures. ,, Other authors provided evidence that the b 2 ion structure could vary with peptide composition. Haeffner and Irikura developed a threshold peak abundance prediction model based on the relative energies of the various amide nitrogen protonation sites of [A 8 R+2H] 2+ .…”
Section: Introductionmentioning
confidence: 99%